Telling stories: engaging critical literacy through urban legends in an English secondary school - Jones, Susan; Chapman, Katie (Emerald, 2017)
Non-dominant voices have been further marginalised in the most recent National Curriculum in England (DfE 2014) and those working across the English teaching profession often find the subject framed according to narrow, assessment driven models and prescribed skill sets. This article brings together two perspectives on the importance of literacy education that remains rooted in young people's everyday experiences of place. Katie is a newly qualified secondary English teacher. She will share examples taken from her own classroom practice of the ways in which she has responded to stories told by young people about the places in which they live. Susan is a tutor of Initial Teacher Education (ITE). She suggests that Katie’s approach provides persuasive exemplification of how engagement with alternatives to a dominant view of literacy should remain a key objective for those working with beginning teachers of English. For Katie's students, urban legends are powerful texts which offer the means to explore what we do when we tell stories, both inside and outside the English classroom. As will be shown, such stories are telling examples of the resources young people can bring to critical literacy learning in current classrooms. In the context of the dominance of a narrow, mandated experience of English as a subject, the imperative becomes even greater to recognise stories such as those shared by Katie's students as opportunities for authentic, creative and critical engagement with text.